Nutritional Quality of Amofer (Ammonia Fermentation) Corn Straw Using EM4 and M21 Decomposer - Fitria, Restuti; Luthfi, Subhanul Arafat Chayatul; Hindratiningrum, Novita (Jurnal Sains dan Teknologi Peternakan, 2023)
This study aimed to identify the best starter levels of commercial cultures and incubation time on crude protein (CP), crude fiber (CF), extract ether (EE), and nitrogen-free extract (NFE) of amofer corn straw. This research used a completely randomized design with ten treatments and four replications. The treatments were the additions of EM4 (EM) and M21 decomposer (MD) at different levels (control/without amofer; 0.04 % EM; 0.06 % EM; 0.04 % MD; and 0.06 % MD) and incubation times (4 weeks and 2 weeks). The obtained data were analyzed by analysis of variance (ANOVA), then continued with the Duncan Multiple Range Test (DMRT). The result showed that the use of commercial starters with different fermentation times could increase the CP and NFE levels while reducing the EE and CF of amofer corn straw. The most effective treatment was the addition of 0,04 % EM and 2 weeks incubation which contained CP of 5.9415 %, CF of 37.8545 %, EE of 4.5183 %, and NFE of 32.4245 %.